COMMON TYPES OF VERBS IN ENGLISH AND UZBEK LANGUAGES - Suyunova Marjona Mingboy qizi; Mukhammadiyev Aziz Shavkatovich (PEDAGOGS, 2024)
Abstract: this article provides an overview of the common types of verbs in the English and Uzbek languages. It examines the similarities and differences in verb classification and usage between the two languages. The key types of verbs discussed include action verbs, linking verbs, and auxiliary verbs. The article aims to enhance the understanding of verbal structures and their applications in both languages.